Use of herbal medicine during pregnancy and associated factors among pregnant women with access to public healthcare in west Shewa zone, Central Ethiopia: sequential mixed-method study - Gemechu Gelan Bekele; Benyam Seifu Woldeyes; Getu Melesie Taye; Ermiyas Mulu Kebede; Delelegn Yilma Gebremichael (BMJ Open, 2024)
Objective This study was aimed at assessing the prevalence of herbal drug use among pregnant women with access to modern medicine and associated factors in public health facilities in the west Shewa zone, Oromia regional state, Ethiopia.Design A sequential mixed-method study approach was carried out among pregnant women and other stakeholders.Setting This study was conducted at public health facilities, including 3 public hospitals and 20 health centres, in the west Shewa zone of Ethiopia.Participants A systematically selected sample of 411 pregnant women was participated in the quantitative study. For the qualitative method, focus group discussions and in-depth interviews were conducted among pregnant women attending antenatal care and key informants using an interview guide until data saturation was achieved.Primary outcome For outcome variables, the respondents were asked if they used any herbal medicine during their current pregnancy. It was then recorded as 0=no and 1=yes.Results The prevalence of herbal medicines was found to be 19.7%. The most commonly used herbal medicines were Zingiber officinale, Ocimum gratissimum, Eucalyptus globules, Allium sativum and Rutacha lepensis. Herbal medicine use during pregnancy was significantly associated with older maternal age (adjusted OR (AOR) 2.4, 95% CI 1.2 to 5.1), urban residence (AOR 2.3, 95% CI 1.3 to 3.7) and second trimester of pregnancy (AOR 2.3, 95% CI 1.3 to 4.5).Conclusions In this study, one in five pregnant women uses herbal medicine, which is relatively low. Sociodemographic factors and the duration of pregnancy affected the utilisation of herbal drugs during pregnancy. The most common herbals used by pregnant women were intended to treat minor disorders of pregnancy and medical disorders such as hypertension.